2012
DOI: 10.3390/cryst2020579
|View full text |Cite
|
Sign up to set email alerts
|

Spin and Charge Transport in the X-ray Irradiated Quasi-2D Layered Compound: κ-(BEDT-TTF)2Cu[N(CN)2]Cl

Abstract: The interplane spin cross relaxation time T x measured by high frequency ESR in X-ray irradiated κ-(BEDT-TTF) 2 Cu[N(CN) 2 ]Cl is compared to the interplane resisitivity ρ ⊥ and the in-plane resistivity ρ between 50 K and 250 K. The irradiation transforms the semiconductor behavior of the non-irradiated crystal into metallic. Irradiation decreases T x , ρ ⊥ and ρ but the ratio T x /ρ ⊥ and ρ ⊥ /ρ remain unchanged between 50 and 250 K. Models describing the unusual defect concentration dependence in κ-(BEDT-TTF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…The minor ESR signal shifts to lower fields and can be clearly identified as a separate maximum below T = 2.5 K. In Figure 66(d) the angular dependence of the ESR signal is displayed, revealing two low-temperature features with a large anisotropy of about 10 mT, which are symmetrically shifted by ±22 • with respect to the main signal. A similar behavior has been reported for κ-(BEDT-TTF) 2 Cu[N(CN) 2 ]Cl, due to crystallographically inequivalent adjacent layers [582][583][584], depicted in Figure 6. For the monoclinic symmetry of κ-(BEDT-TTF) 2 Cu 2 (CN) 3 , this explanation does not hold; hence stacking faults in the crystal are suggested to cause the doubling of the line.…”
Section: Valence-bond Solidsupporting
confidence: 82%
“…The minor ESR signal shifts to lower fields and can be clearly identified as a separate maximum below T = 2.5 K. In Figure 66(d) the angular dependence of the ESR signal is displayed, revealing two low-temperature features with a large anisotropy of about 10 mT, which are symmetrically shifted by ±22 • with respect to the main signal. A similar behavior has been reported for κ-(BEDT-TTF) 2 Cu[N(CN) 2 ]Cl, due to crystallographically inequivalent adjacent layers [582][583][584], depicted in Figure 6. For the monoclinic symmetry of κ-(BEDT-TTF) 2 Cu 2 (CN) 3 , this explanation does not hold; hence stacking faults in the crystal are suggested to cause the doubling of the line.…”
Section: Valence-bond Solidsupporting
confidence: 82%
“…Actually, the molecular disorder introduced by X-ray irradiation to the organic superconductor κ-(BEDT-TTF) 2 Cu(NCS) 2 increases the residual resistivity, and suppresses the superconductivity [18,27]. We investigated the X-ray irradiation effect widely in κ-(BEDT-TTF) 2 X showing superconductivity or Mott insulating state from the viewpoint of the relation between the correlated electronic states and randomness [20,[27][28][29][30][31][32][33][34]. Recently, we found that the weak molecular disorder introduced by X-ray irradiation of the organic superconductor κ-(BEDT-TTF) 2 Cu[N(CN) 2 ]Br induced the Anderson-type localization insulating state from the strongly correlated metallic/superconducting state [31].…”
Section: Introductionmentioning
confidence: 99%
“…By now, there are various studies which have utilized X-ray irradiation to probe the interplay of disorder and correlations close to the Mott transition in κ-phase chargetransfer salts [139,140,[147][148][149][150][151][152][153][154][155][156]. In fact, the corresponding Mott-Anderson model has attracted significant attention from a theoretical perspective, leading to a large number of numerical evaluations of its properties (e.g., Refs.…”
Section: Experimental Study Of Phenomena Close To the Mott Transition...mentioning
confidence: 99%